2010
DOI: 10.1002/hed.21360
|View full text |Cite
|
Sign up to set email alerts
|

Chemoradiotherapy for locoregionally advanced squamous cell carcinoma of the base of tongue

Abstract: Concurrent chemoradiotherapy results in promising locoregional control for base of tongue cancer. As distant relapse was common, further investigation of systemic therapy with novel agents may be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 53 publications
(42 reference statements)
2
18
0
Order By: Relevance
“…The rate of distant metastases in HPV+ patients can remain high, despite control of local disease. This is consistent with previous studies [14,18]. In our cohort, 4 (15.4%) out of 26 patients experienced distant recurrence, with the lung being the most common site of recurrence.…”
Section: Discussionsupporting
confidence: 93%
“…The rate of distant metastases in HPV+ patients can remain high, despite control of local disease. This is consistent with previous studies [14,18]. In our cohort, 4 (15.4%) out of 26 patients experienced distant recurrence, with the lung being the most common site of recurrence.…”
Section: Discussionsupporting
confidence: 93%
“…McDowell et al [20] concluded that chemoradiotherapy may be a reasonable alternative to surgery in patients with T4 tongue cancer, while Stenson et al [21] reported that systemic chemoradiotherapy in such patients may negate the need for total glossectomy. Pederson et al [22] reported that the rates of 5-year locoregional progression-free survival, overall survival, and disease-free survival in 127 patients with stage III or IV base of tongue cancer treated with systemic chemoradiotherapy was 87, 58.2, and 46 %, respectively. Concurrent chemoradiotherapy offers promising locoregional control for base of the tongue cancer [22].…”
Section: Discussionmentioning
confidence: 99%
“…Pederson et al [22] reported that the rates of 5-year locoregional progression-free survival, overall survival, and disease-free survival in 127 patients with stage III or IV base of tongue cancer treated with systemic chemoradiotherapy was 87, 58.2, and 46 %, respectively. Concurrent chemoradiotherapy offers promising locoregional control for base of the tongue cancer [22]. Another option for advanced tongue cancer is intra-arterial chemoradiotherapy, especially superselective intra-arterial infusion [17,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Denis et al reported that RT plus chemotherapy may be more effective than RT alone in the setting of advanced stage tumors. However, both RT alone and RT plus chemotherapy have been associated with long-term complications such as dysphagia and pharyngeal strictures [10, 11]. The more recent introduction of transoral surgical strategies has been temporally associated with an upswing in the proportion of patients receiving primary surgery [12].…”
Section: Introductionmentioning
confidence: 99%